Early response in antibacterial activity of orthopaedic metal implant coated with silver composite as future implant related infection treatment – Preliminary result - Mohd Jan, Nurul Hafiza; Zulkifly, Ahmad Hafiz; Ibrahim, Mohd Zulfadzli; Shaban, Munirah (2017)
INTRODUCTION: The prevalence of implant associated with infection remains high. The management of this incidence poses a major challenge in orthopaedic field since these scenarios are chronic and biofilm based. Colonization of bacterial and biofilm adhesion on implant may lead to infection at underlying bone and surrounding tissues. Surgically device removal and addition with prolonged used of antimicrobial theraphy are leads to patient suffering, substantial morbidity and even mortality. Hence, to overcome this, alternative treatment strategy using orthopaedic metallic implant coated with 3% silver was introduced. The 3% silver composite exhibits good bactericidal properties. It inhibits biofilm formation particularly, at the adhesion stage of the relevant bacteria. Hence, the aim of this study is to investigate the potential effect of silver coated orthopaedic metal implant against biofilm-producing Staphylococcus aureus through in vitro experimental setting.